Large Data-Handling Equipment as a Commercial Tool - Postley, John A. (Management Science, 1957)
The primary purpose of this paper is to present for management an approach to the employment of large data-handling equipment in commercial problems. This approach is in the form of guideposts which, in a very general way, may indicate to people without a background in the data processing field, major requirements to consider or problems which will be encountered in connection with this employment. The problem arises in the military departments largely in connection with logistics and throughout non-military governmental and nongovernmental operations.